Cottonseed protein concentrate as an effective substitute to fish meal in pike perch (Sander luciperca) feed: evidence from growth performance and intestinal responses of immune function and microflora - Fan, Ze; Zhao, Jie; Huang, Jiaming; Lu, Cuiyun; Wu, Di; Sun, Zhipeng; Li, Jinnan; Wang, Liansheng; Zheng, Xianhu (Frontiers in Immunology, 2025)
IntroductionThe aim of this study was to assess the response characteristics of intestinal immune function and microflora of pike perch (Sander luciperca) receiving cottonseed protein concentrate (CPC) as a substitute for fishmeal.MethodsA basal diet was formulated to contain 55% fish meal, and then CPC was used to replace 0% (CPC0), 20% (CPC1), 40% (CPC2), and 60% (CPC3) of dietary fish meal. The four diets were fed to pikeperch with an initial body weight of 3.55 ± 0.01 g for 8 weeks.ResultsThe results revealed that there were no significant effects of dietary CPC levels on survival rate, mass gain rate, and specific growth rate. The highest value for the feeding efficiency ratio was found in the CPC3 group and was significantly higher than that of the control group. Significantly lower values for the hepatosomatic index, crude ash content, and higher crude protein content were observed in the CPC3 group. Trypsin activity in the CPC3 group was lowest compared to the control group and CPC1 group. Among the three CPC substitution groups, increases in intestinal antioxidant enzyme activities, glutathione content, and anti-inflammatory factor expression, and downregulation of pro-inflammatory factors were observed with increasing CPC substitution. The injury degree of the intestinal mechanical barrier was mitigated along with relief of oxidative damage and inflammation with increasing CPC substitution ratios.Discussion and conclusionIn conclusion, 60% of fish meal can be replaced by CPC based on the above results. However, increasing dietary CPC substitution slightly increased Firmicutes abundance and significantly decreased Actinobacteriota abundance, but the abundance of Proteobacteria in the CPC3 group was appreciably increased. An increase in Staphylococcus and a reduction of Lactobacillus were observed in the CPC2 and CPC3 groups. Igf1 expression was significantly downregulated with increasing CPC substitution. Henceforth, the above two limiting factors should be considered key breakthroughs in improving the effectiveness of replacing fish meal with CPC in pikeperch. The current findings provide a significant reference and breakthrough in improving the effectiveness of replacing fishmeal with CPC in pikeperch diets.